Enhancement of the measurement method for the radar cross section of unmanned aerial vehicles in the X-band under anechoic chamber conditions - Popov, Anatoliy; Vorobiov, Iurii; Maiorova, Kateryna; Bortsova, Mariya (Technology audit and production reserves, 2026)
The object of research is the process of measuring the effective scattering surface of an unmanned aerial vehicle (UAV) in the X-band of electromagnetic waves in an anechoic chamber. The problem being solved is to obtain reliable initial data for assessing the radar visibility and probability of detecting UAVs based on their backscatter diagrams. The aim of research is to improve the method of measuring the effective scattering surface (ESS) of UAV components in the X-band in an anechoic chamber and its experimental testing. As a result of the research, a technology for measuring the angular dependence of the ESS in the X-band was formed, which includes compensation of the background signal, calibration of the measuring equipment, ESS determination of the object and automation of the measurement process. The technology includes the design of the anechoic chamber, the structure of the measuring stand, the method of compensation of the background reflection, measurement of the reflected signal power, calibration of the measuring equipment, ESS calculation. The conducted field experiments allowed to obtain the characteristics of the secondary scattering of UAV components in the angle sector ±45°, while the measurement error of static reference objects did not exceed ±1 dB. Comparison of experimental results with the data of mathematical modeling based on integral equations and the physical theory of diffraction confirmed the reliability of the improved approach. The obtained results can be used to increase the accuracy of assessing the radar visibility of small-sized UAVs and improve the means of their detection.